(untitled) (Semiárida, 2020)
Maize is high quality summer forage and very commonly used because 01 simple cultivation and management. It can be used during an ample period, from green forage untill maturity. The availability 01 forage dry matter increases during the growth period, being highest at grain setting. While the stages previous to flowerinq are most adequate to leed bull calves, in milky or doughy grain stage it becomes very gooo forage to fatten young bulls, cows and heilers. Literature mentions the existence 01 variability in tillering maize populations with the capacity 01 re-growth after stalk formation, concluding that it would be possible to advance by selection in order to obtain double purpose maize, adapted for grazing. The objective of this work is to compare a tillering population obtained from the crosses between Zea mays x Zea diploperennis, to a commercial hybrid in terms 01 dry matter production, silage and grazing use. The working hypothesis is that the perennial ancestor transmits higher re-growth capacity to the hybrid. The Population 3 F.A. and a commercial hybrid, were grown in a completely randomized block design with four repetitions. Each plot consisted 01 eight plots (two genotypes and four harvest dates) in four rows with plants spaced 30 cm within the row and 70 cm between rows. Total dry matter production and its components were registered at 30, 52, n and 117 days after emergence (dde). The plants were harvested 15 cm above the soil surface and separated into stover and husked ears. Test "t" was used to determine statistical differences between genotypes at each harvest date. At the time of the first harvest (30 days after emergency), total leaf dry weight (kglha) 01 the experimental population was significantly higher than that of the comercial hybrid, and at doughy maturity (117bdde) the experimental population’s leal- and stem production were superior to the commercial hybrid. The production at the earliest harvest date and re-growth, were superior in the experimental population, suggesting that grazing would show best results during the initial phase of the crop, before apical differentiation setts in.